Posttranslational regulation of transporters important for symbiotic interactions. Issue 2 (27th November 2021) - McDonald, Tami R; Rizvi, Madeeha F; Ruiter, Bretton L; Roy, Rahul; Reinders, Anke; Ward, John M
Abstract: Coordinated sharing of nutritional resources is a central feature of symbiotic interactions, and, despite the importance of this topic, many questions remain concerning the identification, activity, and regulation of transporter proteins involved. Recent progress in obtaining genome and transcriptome sequences for symbiotic organisms provides a wealth of information on plant, fungal, and bacterial transporters that can be applied to these questions. In this update, we focus on legume–rhizobia and mycorrhizal symbioses and how transporters at the symbiotic interfaces can be regulated at the protein level. We point out areas where more research is needed and ways that an understanding of transporter mechanism and energetics can focus hypotheses. Protein phosphorylation is a predominant mechanism of posttranslational regulation of transporters in general and at the symbiotic interface specifically. Other mechanisms of transporter regulation, such as protein–protein interaction, including transporter multimerization, polar localization, and regulation by pH and membrane potential are also important at the symbiotic interface. Most of the transporters that function in the symbiotic interface are members of transporter families; we bring in relevant information on posttranslational regulation within transporter families to help generate hypotheses for transporter regulation at the symbiotic interface. Abstract : Regulation of transport proteins involved in mycorrhizal and rhizobial symbioses is best understood by incorporating what is known about regulation of related transporter proteins in the same family.